Market instruments and the protection of natural resources - Stoianoff, Natalie P.; Kreiser, Lawrence A.; Butcher, Bill.; Milne, Janet E.; Ashiabor, Hope.; Edward Elgar Publishing (Northampton, MA : Edward Elgar Pub., 2016)
Only through a concerted global effort can we protect our natural resources, save our precious natural environment, and indeed our future. Pressures on our natural environment come from many directions, including overuse, mismanagement and contamination, all of which must be addressed through a range of measures as part of an international response. This much-needed book reviews and evaluates the use of market and fiscal instruments in protecting our natural resources, from rural to marine environments. The expert contributors emphasise the need to reduce greenhouse gas emissions to stem the tide of irreparable harm to our natural resources. Market instruments that are designed to protect the global atmosphere are evaluated, along with carbon instruments and environmental tax incentives. Meanwhile, consideration is given to shifting the tax burden to achieve environmentally responsible outcomes, balancing sustainable use and natural resource protection, and protecting water resources. Offering a comprehensive appraisal of market instruments and policy solutions for natural resource protection, this book is ideal for both policy makers and students and academics of environmental law, economics and sustainability.
Preface -- Part I balancing sustainable use and natural resource protection -- 1. The use of market based instruments in protecting south Australia's marine protected areas / Karen Bubna-Litic -- 2. A bottom up approach to developing REDD+ programs in Brazilian states and California / Ana Carolina Cerqueira Duque -- 3. Sowing the seed of change: why Australia's land sector needs a carbon price to encourage mitigation of ghg emissions and promote sustainable land use / Vanessa Johnston -- Part II protecting water resources -- 4. Fighting for water: the role of federal market instruments in addressing water issues the United States / Mona L. Hymel -- 5. The impact of hydraulic fracturing on fresh water resources in the United States / Hans Sprohge, Bill Butcher and Mary Margaret Callison and Larry Kreiser -- 6. A quantitative analysis of tax incentive policy to support water conservation and protect the ecosystem / Rahmat Tavallali and Paul Lee -- Part III shifting the tax burden to effect environmentally responsible outcomes -- 7. From fossil fuels to renewable energy: subsidy reform and energy transitions in African and Indian Ocean island states / Kai Schlegelmilch, Jacqueline Cottrell and Francois Fortier -- 8. Using environmental taxation to improve outcomes for e-waste in Australia / Wayne Gumley -- 9. The ad unit and ad valorem tax burden shifting and its impact on pigovian taxation in the European Union member states / Danuse Nerudova and Marian Dobranschi -- Part IV evaluating instruments that protect the global atmosphere -- 10. Carbon trading or carbon tax: which is the more feasible solution to climate change from the perspective of China? / Mingde Cao -- 11. Regulation of ship-sourced carbon dioxide emissions: the creation of economic instruments / Stathis Palassis -- 12. Sectoral allocation patterns in the EU emission trading scheme: empirical evidence and outlook / Claudia Kettner -- 13. Paris: the dilemmas of international climate change negotiations and the role for linked emissions trading schemes in the post 2020 regime / Elena De Lemos Pinto Aydos -- 14. Just ETS? social justice and recent reforms in EU and US carbon markets / Achim Lerch and Sven Rudolph.
Contributors include: K. Bubna-Litic, B. Butcher, M.M. Callison, M. Cao, A.C. Cerqueira Duque, J. Cottrell, E. de Lemos Pinto Aydos, M. Dobranschi, F. Fortier, W. Gumley, M.L. Hymel, V. Johnston, C. Kettner, L. Kreiser, P. Lee, A. Lerch, D. Nerudova, S. Palassis, S. Rudolph, K. Schlegelmilch, H. Sprohge, R. Tavallali.
Includes bibliographical references and index.
Description based on print record.
Keywords: Environmental impact charges; Conservation of natural resources; Electronic books